Implementasi Good Governance di Kecamatan Sabangau Kota Palangka Raya - Muhamad Yusuf (Pencerah Publik, 2015)
In the authors use a qualitative approach. According to Sugiyono (2011:8) "Qualitative research method is a method used to examine the condition of natural objects". The Dimanapeneliti is as a key instrument, the data collection techniques are done triangulated (combined), inductive data analysis, and the results of qualitative research emphasizes the meaning of generalization. Based on the theory, researchers are used to using qualitative research methods because they want to understand sociological factors, situations, and symptoms or social phenomena in depth, and in a comprehensive sense. With a qualitative approach, researchers do research on natural settings, meaning researchers see the fact that there is field. In this case, researchers observe governance in Sabangau sub-district in government administration